Pengaruh Proftabilitas, Solvabilitas, Ukuran Perusahaan dan Reputasi Auditor Terhadap Audit report lag pada Sektor Pertambangan yang Terdapat pada Bursa Efek Indonesia Periode 2017-2021 - Hendrick Yohannes Wijaya Tamba; Tetty Tiurma Sipahutar (Jurnal Indonesia Sosial Sains, 2022)
Financial reports are a tool used as a tool or assessor of company performance and also encourage the development of companies, especially companies that have been listed on the stock exchange. Some of the characteristics of good financial statements are that they are easy to understand, appropriate, materiality, have the capacity of reliability, and can be compared with others. This study aims to evaluate and analyze the effect of profitability, fairness, firm size and KAP on delays in audit reports in the mining sector of the Indonesia Stock Exchange for the 2017-2020 period. This study is a descriptive statistical study. A sample of 100 companies were selected using purposive sampling. The data used is secondary data using multiple linear regression data analysis. Based on the results of the study indicate that profitability, solvency, and firm size have no effect on Audit Report Lag. Auditor reputation has an effect on Audit Report Lag. Profitability, solvency, firm size, and KAP reputation have a simultaneous effect because the significant value is 0.019, which means the value is <0.05.